Flourishing and learning engagement: the importance of personal best goals - Awang, Nurul Afiqah; Mohd Mahudin, Nor Diana (Universiti Putra Malaysia Press, 2023)
Despite a growing literature on learning engagement, its relationship with flourishing has had little attention, and even less has been given to the role of personal best goals in university students. Addressing these gaps, this study investigated the relationship between flourishing and learning engagement through the mediating role of personal best goals. Data were collected via an online survey from a sample of 206 university students from various higher education institutions in Malaysia. The associations among the variables were evaluated using correlational analyses, while nonparametric bootstrapping procedures using PROCESS within IBM SPSS were used to test for mediation effects. Results showed that flourishing is positively associated with learning engagement and personal best goals, while personal best goals are significantly related to learning engagement. Both flourishing and personal best goals are also significant predictors of learning engagement. In addition, personal best goals mediated the relationship between flourishing and learning engagement, in which there is a significant indirect effect of flourishing on learning engagement via personal best goals. These results highlight the vital role of personal best goals as one of the mechanisms by which flourishing may affect learning engagement. They also shed light on the potential implications of flourishing and personal best goals in optimising students’ learning in higher education.